Validity and reliability of the portuguese version of the Healthy Lifestyle Questionnaire—EVS III - Batista, Marco (2022)
The main objective of this study was to validate the Healthy Lifestyle Questionnaire—EVS III, using confirmatory factor analysis of the measurement model. A total of 822 Portuguese individuals of both genders, aged between 18 and 66 years old (M = 28.43 SD = 12.07), participated in this study, of which 382 were male (46.5%) and 440 were female (53.5%). The main results obtained revealed that the psychometric qualities prove the adequacy of the factor structure of the Healthy Lifestyles Questionnaire—EVS III (7 factors/32 items) and that it has acceptable validity indices: χ2 = 644.6828, p = 0.000, df = 168, χ2 = 3.84, NFI = 0.901, TLI = 0.902, CFI = 0.921, IFI = 0.922, MFI = 0.900, GFI = 0.909, AGFI = 0.901, RMR = 0.073, SRMR = 0.059 and RMSEA = 0.059, enabling the assessment of factors related to a balanced diet, respect for mealtimes, tobacco consumption, alcohol consumption, consumption of other drugs, resting habits and physical activity habits. The Portuguese version of the Healthy Lifestyles Questionnaire—EVS III can be used with reasonable confidence for the assessment of healthy lifestyles.